RELAKSASI AUTOGENIK MENURUNKAN KADAR GULA DARAH PASIEN DIABETES MELITUS TIPE 2 - Wahyuni, Aria; Kartika, Imelda Rahmayunia; Pratiwi, Amira (REAL in Nursing Journal, 2018)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia resulting from a lack of insulin secretion, insulin action, or both. The aim of the study was to determine the effect of autogenic relaxation on the reduction of blood sugar levels in Type 2 Diabetes Mellitus Patients. The research design used was Quasi Experimental with the Pretest-Posttest approach method. This research was conducted in one of the work areas of the health center in the city of Bukittinggi in June-July 2108. The population of this study was all patients with type 2 DM totaling 150 people while the samples taken were 15 people with a purposive sampling technique. The analysis used is univariate and bivariate analysis using the dependent t-test. The results of this study found that the average blood sugar level before the autogenic relaxation intervention was 214.4 gr/dl, the average blood sugar level after autogenic relaxation was 205 gr/dl with a p value = 0,000 meaning that there was an effect of autogenic relaxation on decreasing levels blood sugar in type 2 DM patients. The recommendation of this study is to continue this study with a large sample and with long and periodic interventions. Keywords: Type 2 Diabetes Mellitus, Blood Sugar Level, Autogenic Relaxation